Creation of a Recognition and Implementation Evaluation Sheet for the Couple Parenting Promotion Program - Shimizu, Yoshiko (British Journal of Healthcare and Medical Research, 2025)
As the final stage of the Grant-in-Aid for Scientific Research project “Development and Evaluation of a Couple Parenting Promotion Plan,” this study finalized the Recognition and Implementation Evaluation Sheet to support the finalization and dissemination of the couple parenting program. In Study 1, we compiled the web-based intervention survey content (4 perspectives, 14 items over 1 week) into a trial version of the sheet on a single A4-sized sheet. The trial sheet’s clarity was assessed through a free-response survey (March 2025) conducted among 378 individuals who had collaborated in the web-based intervention survey. These participants were parents aged 25–38 years who were raising children aged 5 years or younger and residing across all Japan prefectures. We then incorporated their feedback in the final version of the sheet. In Study 2, we verified the finalized sheet’s effectiveness. To focus on implementation points, both partners used the finalized sheet in implementing all items (dividing the 4 perspectives into 2, each implemented for 2 weeks, totaling 4 weeks). Effectiveness was verified by examining changes in the shortened version of the Couple Parenting Awareness Scale item scores (5-point scale) before and after the intervention. Simultaneously, participants provided free-response evaluations of the sheet. In total, 473 individuals voluntarily participated, meeting the same eligibility criteria as those in Study 1. Using the finalized sheet, we observed improvements in couple parenting, showing significant increases in 11 of 15 sub-items across all four scale items. Interventions using the trial sheet yielded significant increases in only three items, with no significant improvements in “Mutual Emotional Support” and “Shared Responsibility and Difficulties.” The latter obtained the lowest scores among the four scale items and acted as a negative factor between scale items.